Managing atrial fibrillation in the very elderly patient: challenges and solutions - Karamichalakis, Nikolaos (Vasc Health Risk Manag, 2015)
Atrial fibrillation (AF) is the most common arrhythmia affecting elderly patients. Management and treatment of AF in this rapidly growing population of older patients involve a comprehensive assessment that includes comorbidities, functional, and social status. The cornerstone in therapy of AF is thromboembolic protection. Anticoagulation therapy has evolved, using conventional or newer medications. Percutaneous left atrial appendage closure is a new invasive procedure evolving as an alternative to systematic anticoagulation therapy. Rate or rhythm control leads to relief in symptoms, fewer hospitalizations, and an improvement in quality of life. Invasive methods, such as catheter ablation, are the new frontier of treatment in maintaining an even sinus rhythm in this particular population.